Analisis Kepribadian Tokoh Utama dalam Novel Gemaya Karya Risma Ridha Anissa (Tinjauan Psikologi Sastra) - Novia Nurkamila; Suntoko Suntoko; Wienike Dinar Pratiwi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the main character in the novel Gemaya by Risma Ridha Anissa using a literary psychology approach. The theory used is Sigmund Freud's literary psychology theory to analyze the personality structure of the main character and the dynamics of the main character's personality. The research approach used is a non-interactive approach and the research method used is descriptive analysis method. The source of the data in this research is the novel Gemaya by Risma Ridha Anissa. The results of this study are the personality of the main character Gehaya with the instinct of life which is described by motivating others. The death instinct is depicted by the choices of others through the character's attitude. Objective anxiety who experiences anxiety will respond to the real thing in front of him, so that it is described with feelings of panic. Neurotic anxiety that is described through the reaction of only the character of Gemaya to the network that is in his mind or imagination. The moral anxiety contained in the character of Gemaya is in the form of being ungrateful for what is not there and causing feelings of envy.